Application of Solar Energy for Coconut Grating Machine in Rural Areas - Husen Asbanu; Yendi Esye; Yefri Chan; Danny Faturachman (The University of Lampung, 2025)
Manual processing of coconut and the expensive gasoline force farmers to sell copra at low prices. This study explores the potential use of solar energy for operating coconut grating machines. The experiment utilized a 100 Wp solar panel to run a coconut grating machine driven using ¼ HP electric motor. The observation parameters included solar irradiance, power, voltage, current, battery charging duration, and energy efficiency. The results indicate that a 100 Wp solar panel is insufficient to meet the power requirements of the 186 W electric motor. Therefore, adding at least two solar panels and increasing the battery capacity must meet the machine's operational requirements. The battery charging time, until complete, is recorded at 16 h. Without the support of solar panels, the battery can operate the machine for 3 to 4 h. Meanwhile, when the battery is recharged while the machine operates with the solar panel system, the operating duration can reach 6 to 7 h. Therefore, solar energy demonstrates great potential as a renewable energy solution that can be utilized in the agricultural processing process in rural areas in a sustainable and environmentally friendly manner. Testing of the coconut grating machine powered by solar energy, supported by a 12V 100Ah battery and a 1/4 HP motor, showed that it can operate for approximately 3.8 h in a single work cycle. With a grating duration of 2.6 min per coconut, the system can grate up to approximately 87 coconuts per operational cycle.